Evaluating a multimodal digital book's impact on ESP students' learning outcomes - Laksana, I Putu Yoga; Padmadewi, Ni Nyoman; Suarcaya, Putu; Utami, I.G.A Lokita Purnamika; Ramendra, Dewa Putu (Journal of English Language Teaching Innovations and Materials (Jeltim), 2024)
The use of digital books in EFL setting has become widespread, eliciting responses. However, the evaluation on the multimodal digital book using a Kirkpatrick model of evaluation is limited. This study focused on the evaluation of the use of multimodal digital book in English for Business Course toward the students"™ English competence and behavioral outcomes. 60 students were involved in this study. The integration of Kirkpatrick evaluation model and mixed-method approach used as the research design. Moreover, interviews were used to acquire qualitative data, while surveys, pre- and post-test results, and performance ratings were used to collect quantitative data. The result showed overwhelming feedback from the students which showed over 85% of the scores on every aspect. Pre-and post-test result then showed a significant result with a large effect size (Cohen's d = 1.917). Furthermore, based on six practical activities and a final project result, the students"™ business English skills were steadily improved. Based on the UTAUT model framed, the students also showed the digital book"™s high levels of acceptability and perceived use. The findings also showed the multimodal digital book challenges conventional methods of teaching ESP.